The Use of the Al-Quran Index from Tafsirweb.com in Speeches by Students at Al Muslim Waru Junior High School in Sidoarjo - Siti Aisyah; Ahmad Munjin Nasih; Mohammad Khasairi (Eduvest - Journal of Universal Studies, 2026)
One of the communication skills in the 21st century is giving speeches. To improve your speech skills, relevant media and strategies are needed. The Al-Quran must be used as a guide for Muslims. Islamic schools currently need technology-based learning tools that are able to search for information effectively, quickly and accurately. This research describes the use of the Al-Quran indexation application tafsirwe.com in preparing speeches and describes strategies for improving the communication skills of Al Muslim Middle School students. This exploratory qualitative research aims to describe alternative new strategies in learning Indonesian, especially speech using digital Al-Quran indexation. Data was obtained from a collection of work from class IX and class VIII students from SMP Al Muslim, then analyzed through coding and interpreting the meaning of the findings as well as reinforced by teacher anecdotes and the results of interviews with the head of the Education division of the Al Muslim Foundation. Through the keywords included in tafsirweb.com, students find a lot of tafsir information as a basis for preparing speech texts. The flow of using tafsirweb.com is classified into three types, all have the same search goal, namely finding letters, verses, meanings, and verse content, but each type has a different function, type 1 uses tafsirweb.com to find ideas, type 2 to look for appropriate references, type 3 to strengthen the contents of the text, the information obtained by students through tafsirweb.com is then developed through persuasive sentences which are formulated through telling strategies, commanding strategies, and forbidding strategies.